BETWEEN INNOVATION AND STATE RESPONSIBILITY: ASPECTS OF THE LEGAL REGULATION OF ARTIFICIAL INTELLIGENCE IN PUBLIC POLICIES - Ferreira, Fátima Conceição de Araújo Alves; de Souza, Isadora Lis Alves Ferreira (Editora Impacto Científico, 2025)
With the technological advancement of artificial intelligence (AI), its gradual consolidation as a strategic instrument in the transformation of Public Administration is evident. In this endeavor, its intensification drives gains in efficiency and innovation in the formulation and execution of public policies. On the other hand, it cannot be overlooked that its use raises significant legal and ethical challenges concerning state responsibility, transparency, algorithmic discrimination, and the protection of fundamental rights. Having observed these issues, the content of this article aims to analyze the legal regulation of AI in public policies from the perspective of the Brazilian legal system, through an approach to constitutional foundations, as well as infra-constitutional legislation that also includes draft laws in progress and international experiences in algorithmic governance. From a critical and comparative perspective, it proposes regulatory guidelines based on principles, risk assessment, human supervision, and transparency, with the aim of reconciling technological innovation, administrative efficiency, and democratic accountability. Thus, it is possible to conclude that AI regulation should be guided by an adaptive legal model that combines innovation and legality, ensuring that the technology is used in line with the values of citizenship, public ethics, and social justice.DOI: https://doi.org/10.56238/edimpacto2025.084-017